The relationship between peripheral immune response and disease severity in SARS‐CoV‐2‐infected subjects: A cross‐sectional study - Walter, Laura Otto; Cardoso, Chandra Chiappin; Santos‐Pirath, Íris Mattos; Costa, Heloisa Zorzi; Gartner, Rafaela; Werle, Isabel; Mohr, Eduarda Talita Bramorski; Rosa, Julia Salvan; Felisberto, Mariano; Kretzer, Iara Fabricia; Masukawa, Ivete Ioshiko; Vanny, Patrícia de Almeida; et al. (Immunology, 2022)
Coronavirus disease 2019 (COVID‐19) is a respiratory infection caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and marked by an intense inflammatory response and immune dysregulation in the most severe cases. In order to better clarify the relationship between peripheral immune system changes and the severity of COVID‐19, this study aimed to evaluate the frequencies and absolute numbers of peripheral subsets of neutrophils, monocytes, and dendritic cells (DCs), in addition to quantifying the levels of inflammatory mediators. One hundred fifty‐seven COVID‐19 patients were stratified into mild, moderate, severe, and critical disease categories. The cellular components and circulating cytokines were assessed by flow cytometry. Nitric oxide (NOx) and myeloperoxidase (MPO) levels were measured by colourimetric tests. COVID‐19 patients presented neutrophilia, with signs of emergency myelopoiesis. Alterations in the monocytic component were observed in patients with moderate to critical illness, with an increase in classical monocytes and a reduction in nonclassical monocytes, in addition to a reduction in the expression of HLA‐DR in all subtypes of monocytes, indicating immunosuppression. DCs, especially plasmacytoid DCs, also showed a large reduction in moderate to critical patients. COVID‐19 patients showed an increase in MPO, interleukin (IL)‐12, IL‐6, IL‐10, and IL‐8, accompanied by a reduction in IL‐17A and NOx. IL‐10 levels ≥14 pg/ml were strongly related to the worst outcome, with a sensitivity of 78·3% and a specificity of 79·1%. The results of this study indicate the presence of systemic effects induced by COVID‐19, which appear to be related to the pathophysiology of the disease, highlighting the potential of IL‐10 as a possible prognostic biomarker for COVID‐19. Coronavirus disease 2019 (COVID‐19) patients presented neutrophilia, with signs of emergency myelopoiesis. Alterations in the monocytic component were observed in patients with moderate to critical illness, with an increase in cMo and a reduction in ncMo, in addition to a reduction in the expression of HLA‐DR in all subtypes of monocytes, indicating immunosuppression. DCs, especially pDCs, also showed a large reduction in moderate to critical patients. COVID‐19 patients showed an increase in MPO, IL‐12, IL‐6, IL‐10 and IL‐8, accompanied by a reduction in IL‐17A and NOx. IL‐10 levels ≥14 pg/ml were strongly related to the worst outcome.